Inflammatory pseudotumor of the liver misdiagnosed as a metastatic tumor of nasopharyngeal carcinoma: a typical case report of mistreatment caused by anchoring bias - Zhao, Zejin; Wang, Jianli; Xiao, Yue; Cui, Miaohang; Li, Jian; Ma, Jing (Frontiers in Medicine, 2025)
This case report describes the clinical process of a patient with a history of nasopharyngeal carcinoma (NPC) who was initially misdiagnosed with a metastatic tumor, later confirmed to be an inflammatory pseudotumor (IPT). The patient was a 68-year-old male individual who was diagnosed with nasopharyngeal carcinoma 4 years ago. The condition was well controlled after regular radiotherapy and chemotherapy. One year ago, a solid mass was found in the left lateral lobe of the liver during routine follow-up. MRI suggested nasopharyngeal carcinoma metastasis. Later, MRI at Peking Union Medical College Hospital also suggested nasopharyngeal carcinoma metastasis. Intrahepatic cholangiocarcinoma was not excluded, and surgical treatment was recommended. Preoperative biopsy was recommended by the multidisciplinary team (MDT); however, the patient declined due to financial constraints and personal preference. The patient underwent laparoscopic left lateral hepatectomy and hilar lymph node dissection at the Affiliated Hospital of Chengde Medical College. Postoperative pathology showed dense infiltration of neutrophils, lymphocytes, and eosinophils, with no malignant components, consistent with an inflammatory pseudotumor. The diagnosis was further confirmed by pathological review and immunohistochemistry at Peking Union Medical College Hospital. The patient recovered well after the operation, and there was no recurrence during 1 year of follow-up. This case suggests that in patients with a history of malignant tumors, even when imaging is highly suspicious of tumors, we should still be vigilant for infectious lesions and avoid anchoring bias. Preoperative biopsy and multidisciplinary comprehensive evaluation (MDT) can help clarify the diagnosis and reduce misdiagnosis and overtreatment.